(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To identify factors associated with knowledge and practices regarding dengue fever prevention among full-time nursing students at Nam Dinh University of Nursing in 2023. Subjects and Methods: A cross-sectional descriptive study was conducted among 440 full-time nursing students at Nam Dinh University of Nursing who had completed the final examination of the Microbiology and Parasitology course. Students were assessed on factors related to their knowledge and practices in dengue fever prevention using a self-administered structured questionnaire, which was developed based on relevant literature and expert consultation. Results: Factors significantly associated with knowledge and practices regarding dengue fever prevention among students included academic year, ethnicity, and level of knowledge (p < 0.05). Conclusion: Academic year, ethnicity, and knowledge were identified as factors influencing students’ knowledge and practices in dengue fever prevention. Students should actively manage their study schedules and seek additional information to enhance their understanding of dengue fever, particularly regarding dengue vaccination and treatment methods.